Syndecan-1 as a severity biomarker for patients with trauma - Suzuki, Keiko; Okada, Hideshi; Sumi, Kazuyuki; Tomita, Hiroyuki; Kobayashi, Ryo; Ishihara, Takuma; Mizuno, Yosuke; Yamaji, Fuminori; Kamidani, Ryo; Miura, Tomotaka; Yasuda, Ryu; Kitagawa, Yuichiro; et al. (Frontiers in Medicine, 2022)
Tissue injury and hemorrhage induced by trauma lead to degradation of the endothelial glycocalyx, causing syndecan-1 (SDC-1) to be shed into the blood. In this study, we investigated whether serum SDC-1 is useful for evaluating trauma severity in patients. A single-center, retrospective, observational study was conducted at Gifu University Hospital. Patients transported to the emergency room for trauma and subsequently admitted to the intensive care unit from January 2019 to December 2021 were enrolled. A linear regression model was constructed to evaluate the association of serum SDC-1 with injury severity score (ISS) and probability of survival (Ps). A total of 76 trauma patients (54 men and 22 women) were analyzed. ISS was significantly associated with serum SDC-1 level in trauma patients. Among the six body regions defined in the AIS used to calculate the ISS score, “chest” and “abdominal or pelvic contents” were significantly associated with serum SDC-1 level, and “extremities or pelvic girdle” also tended to show an association with serum SDC-1 level. Moreover, increasing serum SDC-1 level was significantly correlated with decreasing Ps. Serum SDC-1 may be a useful biomarker for monitoring the severity of trauma in patients. Further large-scale studies are warranted to verify these results.